Diversidade funcional e estrutura da comunidade de besouros rola-bostas (Coleoptera: Scarabaeinae) em diferentes ambientes do Pantanal de Poconé - Pessoa, Marcelo Bruno (2013)
The functional diversity refers to the components of biodiversity that influence ecosystem functioning. The relationships of functional diversity wit disturbance can reveal patterns that elucidate the functional stability of environments. In this study we sought to identify the species of dung beetles occurring in the Pantanal, understand how communities are structured functionally and understand the effects of flooding in the functional diversity of dung beetles (Coleoptera: Scarabaeinae). Scarabaeinae beetles were collected in baited pitfall traps into three different areas of the Pantanal (Site 1, Site 2 and Site 3), each containing environments flooded and not flooded. To identify the functional groups present in the community, nine functional attributes of species were measured. Through the measured attributes we obtained the following estimators of functional diversity: functional richness, functional evenness, functional divergence and RAO index. 25278 individuals were collected, belonging to 35 species and 17 genera. We identified eight functional groups. There were structural and functional differences between all areas. Only functional evenness did not differ between areas and between environments. Site 1 showed the structural difference between the environments as well as the site 2. The area with the lowest intensity of flooding showed greater functional difference. Thus, it is concluded that the Pantanal has a diversity comprises species of wide distribution, predominantly cerrado and chaco. Functional groups were defined by the behavior of horizontal displacement, nest type, activity schedule and diet. The intensity of flooding may influence the processes of migration and recolonization of flooded and non-flooded environments in the Pantanal. The similarity of evenness can be an effect of functional asymmetry existing in the community of these beetles.